Research on the Controlled Boiler Variator - 纪岗昌; 杨耀锋; 梁治国 (Jixie chuandong)
Based on the analysis of two kinds of the controlled boiler variator, the kinematics and the dynamics of the selected variator are discussed in this paper. The formulations of it’s efficiency and torgue are given.